(3GdSOGSjGJ GdeNQLI ef SeGYGJ CHj YHO Gddg eMeO Hf CMeO Hf EHQGgje GdQGRi (B- (3GHf GdUjQais - (3CMeO Hf eMeO Hf pSndaI GdCUHgGfj, UOQ GdOjf, CHh WGgQ GdpqSndaj , J (B576 (3g` s; (3GdSdaj , CMeO Hf eMeO Hf Sdag GdCUHgGfj, UOQ GdOjf CHh WGgQ,J (B576 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe CHh WGdH CMeO Hf GdeSde GdJfhNi hHYO agPg CMGOjK ef eSehYGJi YhGd Hjfi hHjf QShd Gddg Udi Gddg Ydjg hSde , ajgG SJI QLGd s
(3BNQgG (B:s
(3MOKfG CHh GdNWGH , bGd (B: (3QCjJ hGKdI Udi Ydi LfGRI acHQ YdjgG CQHYG gPG BNQ GdSOGSjGJ s
(3GdfSNI HgG MhGTs
(3HChd GdfSNI hBNQgG SeGYGJ hbQGBJ cKjQI hNWhW YdeGA GdbQf GdSGHY efge GdMGaX GdOejGWis
(3hGHf QhGL hHYV gPg GdbQGBJ SfI (B631 (3hHYVgG SfI (B640s
(3JHUQI GdYfhGf (B:s
(3JNQjLs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs